A generalized variable neighborhood search algorithm for the talent scheduling problem. (December 2018) - Ranjbar, Mohammad; Kazemi, Ahmad
Highlights: We consider the talent scheduling problem. We develop a linear integer programming model for the problem. We develop a generalized variable neighborhood search algorithm for the problem. Using computational results, we indicate our developed algorithm is efficient. Abstract: An important part of the movie production process is to determine a shooting sequence of scenes to minimize the total cost of the actors, called the talent scheduling problem. We first modify a previously developed formulation of the problem as an integer linear programming model and develop a metaheuristic based on the generalized variable neighborhood search algorithm to solve it. The computational experiments based upon available test instances in the literature suggest that our algorithm outperforms previously developed algorithms especially for large-scale instances.